Bilateral, fused pelvic, ectopic, laterally rotated kidneys: A case report - Kingsley Iyoko Iseko, MBBS(Ib), FWACS (Radiology Case Reports, 2020)
Bilateral fused ectopic pelvic kidneys with lateral rotation abnormality in both kidneys is a fortuitous developmental renal anomaly that to the best of our knowledge this is the first report of this rare anomaly in English literature. Due to the morphologic appearance of this anomaly it is likely it could contribute to the individual remaining asymptomatic therefore discovered incidentally. We present a 42-year-old male who presented with acute unilateral flank pain and incidentally discovered this rare renal anomaly which is an important diagnosis for management by both radiologists and urologists.